Challenges and opportunities for the sustainable development of cattle raising in Brazil - Eustáquio José Reis (Institute for Applied Economic Research (ipea), 2016)
The paper provides historical and analytical perspectives for the assessment of the challenges and opportunities of cattle raising activities in the transition towards a lowcarbon agriculture in Brazil. It is organized as follows. The next section presents long run historical perspectives on the development of cattle raising in Brazil. The third section analyzes the patterns of growth of cattle raising in Brazil based upon municipal panel data of Agricultural Census from 1975 to 2006. The fourth section uses a framework analogous to Hayami and Ruttan (1985) to estimate growth convergence equations for major aspects of cattle raising activities, namely the stocking ratio, the specialization in cattle and farm expansion. The report concludes with a discussion of policy options for a transition towards sustainable cattle raising in Brazil.
Keywords: Q15; Q23; C33; 330; panel data; Arrellano-Bond; agricultural economics; land use; cattle ranching; deforestation